Effect of Fish Curse on Post Caesarean Wound Healing at Dr. Shodiq Jember Clinic - Yuanita Mardiana; Raden Maria Veronika Widiatrilupi (International Journal Of Health Science, 2025)
Background: Both medical and non-medical approaches can be used to post-cesarean care for wound healing. Changing the bandage on the surgical site once a day is an example of medical post-sc care. This study aims to determine the effects of giving catfish to patients who have had caesarean sections. Methods: This study had 27 people and employed a quasi-experimental non-equivalent research design. Ho is rejected and Ha is accepted when a statistical test using the Wilcoxon Test produces a p value of 0.000, where p value (0.000) is less than 0.05. It may be concluded that catfish extract at the Dr. Shodiq Jember Clinic works well to speed up the healing process of SC wounds. Conclusion: Giving kutuk fish extract is effective for healing post-CS wounds. This is because kutuk fish is easier for the body to digest, and has a higher albumin content than eggs. The high albumin protein content in kutuk fish makes this fish effective for the wound healing process. The phenomenon in society, since long ago, people believe that kutuk fish can accelerate the wound healing process, however, some people dislike or are hesitant to eat kutuk fish due to its fishy flavor and odor, therefore kutuk fish extract obtained through such a process, it will be easier for people to consume it, and the wound healing process will run.